Antioxidant Role and Cardiolipin Remodeling by Redox-Activated Mitochondrial Ca2+-Independent Phospholipase A2γ in the Brain - Pavla Průchová; Klára Gotvaldová; Katarína Smolková; Lukáš Alán; Blanka Holendová; Jan Tauber; Alexander Galkin; Petr Ježek; Martin Jabůrek (MDPI AG, 2022)
Mitochondrial Ca2+-independent phospholipase A2γ (iPLA2γ/PNPLA8) was previously shown to be directly activated by H2O2 and release free fatty acids (FAs) for FA-dependent H+ transport mediated by the adenine nucleotide translocase (ANT) or uncoupling protein 2 (UCP2). The resulting mild mitochondrial uncoupling and consequent partial attenuation of mitochondrial superoxide production lead to an antioxidant effect. However, the antioxidant role of iPLA2γ in the brain is not completely understood. Here, using wild-type and iPLA2γ-KO mice, we demonstrate the ability of tert-butylhydroperoxide (TBHP) to activate iPLA2γ in isolated brain mitochondria, with consequent liberation of FAs and lysophospholipids. The liberated FA caused an increase in respiratory rate, which was fully inhibited by carboxyatractyloside (CATR), a specific inhibitor of ANT. Employing detailed lipidomic analysis, we also demonstrate a typical cleavage pattern for TBHP-activated iPLA2γ, reflecting cleavage of glycerophospholipids from both sn-1 and sn-2 positions releasing saturated FAs, monoenoic FAs, and predominant polyunsaturated FAs. The acute antioxidant role of iPLA2γ-released FAs is supported by monitoring both intramitochondrial superoxide and extramitochondrial H2O2 release. We also show that iPLA2γ-KO mice were more sensitive to stimulation by pro-inflammatory lipopolysaccharide, as reflected by the concomitant increase in protein carbonyls in the brain and pro-inflammatory IL-6 release in the serum. These data support the antioxidant and anti-inflammatory role of iPLA2γ in vivo. Our data also reveal a substantial decrease of several high molecular weight cardiolipin (CL) species and accumulation of low molecular weight CL species in brain mitochondria of iPLA2γ-KO mice. Collectively, our results support a key role of iPLA2γ in the remodeling of lower molecular weight immature cardiolipins with predominantly saturated acyl chains to high molecular weight mature cardiolipins with highly unsaturated PUFA acyl chains, typical for the brain.